TEKNOLOGI COMBINED HEAT AND POWER DI INDONESIA - Muhammad Ramlan (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
With the complicated problems faced by The State Electricity Company (PLN)nowadays, the writer would support analyzing for solving problem with the Assessment for Combined Heat and Power (CHP) in Indonesia. CHP Technology/Cogeneration is a technology not produce carbon, so this technology will help Government Policy for reducing carbon emission and environment sustainability. This project has done together among BPP Teknologi (Directorate KKE and UPT LSDE) and Ciptakarya Hasta Paramita Cooperative with Grant budget from UNDP-GEF and supporting budgetDIP.